Product quality, price, and service quality on customer satisfaction analysis at Ananta Photo Medan - Lambok Manurung; Etty Harya Ningsi (Jurnal Ekonomi, 2024)
This study aims to assess and analyze how product quality (X1), price (X2), and service quality (X3) impact customer satisfaction (Y) at Ananta Photo. The research involved 100 participants and employed questionnaire-based data collection. Statistical analysis was conducted using SPSS 23.0 for Windows, including classic assumption tests, multiple linear regression analysis, and hypothesis testing. The results yielded a regression equation: Y = 0.146 + 0.160X1 + 0.209X2 + 0.150X3. Findings revealed that product quality (X1) has a partially positive and significant influence on customer satisfaction (Y) at Ananta Photo, as indicated by a t-value (2.215) > t-table (1.66571) and sig (0.030) < 0.05. Similarly, price (X2) and service quality (X3) also showed partial positive and significant effects on customer satisfaction (Y). The simultaneous examination of these variables indicated a significant positive impact on customer satisfaction (Y) at Ananta Photo. The coefficient of determination reached 0.669, suggesting that 66.9% of the variability in customer satisfaction (Y) can be explained by the independent variables, while the remaining 34.1% is influenced by other factors not examined in the study.